Analisis Politik Hukum Pertanahan Terhadap Perlindungan Data Sertifikat Elektronik - Wirawan, Angeline; Melieyani Susanto; Melisa Pranata; Vanesa Yustira; Presilia Tangriawan; Audry Natalia S; Felicia (Magister Kenotariatan Universitas Surabaya, 2025)
Technological advancements and digital breakthroughs have prompted the Ministry of Agrarian Affairs and Spatial Planning, in collaboration with the National Land Agency, to modernize land administration by implementing electronic land registration through digital certificates. In 2021, the introduction of Electronic Land Certificates (STE) began with the release of Regulation Number 1 of 2021 by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. This regulation was subsequently replaced and updated with Regulation Number 3 of 2023, focusing on the issuance of digital documents within land registration processes. Despite its benefits, this innovation has introduced new challenges, particularly in addressing the risks associated with cybercrime. One significant threat is the potential loss of an electronic certificate due to hacking. To address these concerns, both vertical and horizontal legal protection is necessary. The minister must ensure that comprehensive legal safeguards are in place, protecting against government interference as well as threats from individuals or other groups in relation to the security of electronic certificates. The research question raised in this paper is whether there is an adequate legal framework regulating the protection system of electronic certificate data stored in electronic vaults. The purpose of this paper is to analyze the political law of land administration regarding electronic certificates and to examine the legal protection of data stored in electronic vaults. This study concludes that the validity and security of electronic land certificates require comprehensive safeguards, including encryption mechanisms and the role of the National Cyber and Crypto Agency (BSSN), to prevent risks of digital loss or manipulation.